PENGARUH PERPUTARAN KAS TERHADAP PROFITABILITAS PADA PABRIK ROTIBEGAWAN BAKERY KOTA SIBOLGA - Pasaribu, Chairunnisa; Tambunan , Yenni Sofiana; Sihite , Tiurlina Hasmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study was to determine and analyze the effect of cash turnover on profitability at the Bengawan Bakery bakery, Sibolga City. The population in this study are all financial reports. The sample in this study is financial report data for the last 5 years, namely 2017 to 2021 in quarters. The research results revealed that the highest increase in cash turnover was in the 4th quarter of 2020 of 7.38 times. And the lowest was in the fourth quarter of 2018 at 2.99 times. It can be analyzed that the Profitability of Bengawan Bakery in Sibolga City shows that the Operating Profit Margin data has fluctuated between 46.9% to 52.9%. R square is also called the coefficient of determination, it can be seen that R square (r2) is 0.339 or 33.9%, which means that the effect of cash turnover on profitability is 33.9%. It is known that the tcount value is greater than ttable 3.041 > 2.101, then Ho is rejected and Haha accepted. This means that the proposed research hypothesis can be accepted